STEMA DE INFORMAÇÕES PARA O GERENCIAMENTO DE EVENTOS E PROCESSOS SELETIVOS - Breunig, Marta; Priedols, Anderson A. M.; Müller, Liris; Lazzarotto, Elenir D. R.; Gerhardt, Lucas; Silva, Filipe D. d.; Júnior, Júlio C. B.; Tietzmann, Dionatan K.; Prauchner, Darlinton C. K.; Boniati, Bruno B. (Salão do Conhecimento, 2013)
Resumo